Shadow Teacher Support and Cognitive Development in Inclusive Primary Education: Dukungan Guru Pendamping dan Perkembangan Kognitif dalam Pendidikan Dasar Inklusif - Masri , Hamidah; Wati, Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Inclusive education requires structured academic assistance to address the diverse learning needs of children with special needs in mainstream schools. Specific Background: In inclusive primary classrooms, shadow teachers play a central role in facilitating learning participation, classroom adaptation, and individualized academic guidance for students with conditions such as ADHD and other developmental differences. Knowledge Gap: Although the presence of shadow teachers is widely implemented, empirical analysis describing their structured pedagogical roles and observed cognitive outcomes in classroom practice remains limited. Aims: This study aims to analyze the role of shadow teachers in supporting cognitive learning processes of students with special needs within an inclusive school setting. Results: The findings indicate that shadow teachers provide individualized assistance, behavioral guidance, instructional adaptation, and coordination with classroom teachers, contributing to improved student engagement, task completion, and observable cognitive progress. Novelty: This study presents an integrated description of shadow teacher practices by linking classroom implementation, behavioral management, and cognitive learning indicators within one analytical framework. Implications: The findings provide practical guidance for inclusive education management, particularly in structuring collaborative teaching models and optimizing professional support systems for students with special needs. Keywords: Inclusive Education, Shadow Teacher, Cognitive Development, Special Needs Students, Classroom Support Key Findings Highlights Individualized academic assistance increases student task engagement and learning participation. Collaborative coordination between classroom and support teachers structures adaptive instruction. Behavioral guidance aligns learning routines with measurable cognitive indicators.